EVALUASI KINERJA SIMPANG BERSINYAL JALAN BANYU URIP - JALAN PASAR KEMBANG DAN PERENCANAAN KOORDINASI SIMPANG BERSINYAL - Mohamad Andre Firmansyah Putra; Ibnu Sholichin; Nugroho Utomo (LPPM Universitas Abdurrab, 2024)
The congestion that occurs at Pasar Kembang street - Diponegoro street and Banyu Urip street - Girilaya street has three intersections that are close together and around the intersection there are various land uses, causing high community activities. The purpose of this study was to determine the traffic performance and ideal time coordination at the signalized intersection of Banyu Urip street - Pasar Kembang street. Primary data required for this study are intersection geometric data, cycle time data, vehicle volume data and vehicle travel time data. Meanwhile, the secondary data in this study are population data and the number of motorized vehicles in Surabaya City. Analysis of signalized intersection performance calculations refers to the 2014 PKJI guidelines. Based on the results of the calculation of the traffic performance of the three intersections, it was found that the degree of saturation (DJ) in the 5-year plan life improvement condition at the first intersection Girilaya street, Banyu Urip street and Diponegoro street was 0.93 (average intersection delay = 81.716 sec/skr). Second Intersection Diponegoro street, Pasar Kembang street and Banyu Urip street amounted to 0.84 (average intersection delay = 43.257 sec/skr). Third Intersection Jalan Pasar Kembang and Jalan Pasar Kembang of 0.94 (average intersection delay = 67.887 sec/skr). The coordination between the three intersections follows the same cycle time determination of 188 seconds.